Ranah Kompetensi Kemampuan Kolaborasi dalam Pemecahan Masalah (Collaborative Problem Solving Skill's) - miksan ansori (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
Collaboration is now a necessity in living the daily work. Both simple and complex work. At school, a student usually works together with his classmates to complete group assignments given by the teacher. One must also work with a solid team if they want to achieve sales targets. Principals, teachers and employees must work hand in hand in advancing their schools with the complexity of the problems they present. Even in the family, each member must be able to work together in living his family life well. Collaboration is no longer a partial activity, but it is needed to be a skill that must be possessed by individuals in the 21st century. As a skill( ability), the collaboration will be very useful when directed in the framework of problem-solving. By collaborating, the problems faced will be easier to find solutions to solve. In this context, the ability to collaborate is better known as Collaborative problem-solving skill's (CPS). The urgency of CPS capability has been realized by educators, governments, scientists and even global thinkers. This is evidenced by the establishment of the CPS as one of the most needed capabilities of the 21st century by the OECD. The high awareness of CPS's ability makes practitioners implement their learning with collaboration strategies between students. Researchers have also experimented a lot on the effectiveness of CPS-based learning as well as things that can improve the ability to collaborate with individuals. However, it is also necessary to examine further how the assessment of learning in achieving cps capability improvement. A good assessment will represent the expected achievement of CPS capability. If the evaluation is not able to represent the achievement of the ability correctly, then it will not be known the extent of the effectiveness of the defence method applied.